1998
DOI: 10.1073/pnas.95.4.1776
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a human liver glycogen phosphorylase inhibitor that lowers blood glucose in vivo

Abstract: An inhibitor of human liver glycogen phosphorylase a (HLGPa) has been identified and characterized in vitro and in vivo. This substance, [R-(R*,S*)]-5-chloro-N-[3-(dimethylamino)-2-hydroxy-3-oxo-1-(phenylmethyl)propyl]-1H-indole-2-carboxamide (CP-91149), inhibited HLGPa with an IC 50 of 0.13 M in the presence of 7.5 mM glucose. CP-91149 resembles caffeine, a known allosteric phosphorylase inhibitor, in that it is 5-to 10-fold less potent in the absence of glucose. Further analysis, however, suggests that CP-91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
211
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(230 citation statements)
references
References 41 publications
(49 reference statements)
15
211
0
4
Order By: Relevance
“…Thus, inhibition of glycogenolysis, as well as activation of glycogen synthesis, may be also involved in increased glycogen content in hepatocytes treated with FR258900. Several inhibitors of glycogen phosphorylase described recently have demonstrated glucose-lowering effects by inhibiting hepatic glucose produciton in type 2 diabetes [9,16]. In the present study, we demonstrated that glycogen phosphorylase inhibitor could activate glycogen synthesis, suggesting that phosphorylase inhibitors should also be effective in promoting hepatic glycogen synthesis in the absorptive state.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Thus, inhibition of glycogenolysis, as well as activation of glycogen synthesis, may be also involved in increased glycogen content in hepatocytes treated with FR258900. Several inhibitors of glycogen phosphorylase described recently have demonstrated glucose-lowering effects by inhibiting hepatic glucose produciton in type 2 diabetes [9,16]. In the present study, we demonstrated that glycogen phosphorylase inhibitor could activate glycogen synthesis, suggesting that phosphorylase inhibitors should also be effective in promoting hepatic glycogen synthesis in the absorptive state.…”
Section: Discussionsupporting
confidence: 68%
“…Glycogen phosphorylase activity was measured in the direction of glycogen synthesis by the release of inorganic phosphate from glucose-1-phosphate in a buffer containing 50 mM Hepes (pH 7.2), 100 mM KCl, 2.5 mM EGTA, 2.5 mM MgCl 2 , 0.5 mM glucose-1-phosphate, and 1 mg/ml glycogen at 25°C. Inorganic phosphate was measured by addition of 1M HCl containing 10 mg/ml ammonium molybdate and 0.38 mg/ml malachite green, and the absorbance was determined at 620 nm [9]. Glycogen synthase kinase-3 (GSK-3) activity was measured according to the method described by Coghlan et al [7] using recombinant GSK-3b (Sigma) and phospho GS-2 peptide (Upstate Biotechnology, Lake Placid, NY) as a substrate.…”
Section: Assays For Key Enzymes In Glycogen Metabolismmentioning
confidence: 99%
“…Glucokinase activators have also been described that reduce the rate of endogenous glucose production by promoting hepatic glucose uptake and stimulating insulin release (24). Direct approaches target key enzymes in glycogenolysis or gluconeogenesis, such as glycogen phosphorylase (25), glucose-6-phosphatase translocase (26), or PEPCK (27). Of these direct inhibitors of endogenous glucose production, to date only glycogen phosphorylase inhibitors have been evaluated clinically.…”
mentioning
confidence: 99%
“…Pharmacological inhibition of excessive glycogen phosphorylase activity is one strategy that has been pursued for the development of new antidiabetic agents (1). Inhibition of glycogen phosphorylase activity reduces glucose production in cell culture (2) and in murine models of type 2 diabetes (1,3,4). Compensating for a failure of insulin's action on hepatic glucose output may be a more logical strategy than stimulating muscle glucose transport (5,6) because a drug promoting muscle glycogen storage is likely to produce a rather short-lived effect in characteristically inactive patients (7), since unused glycogen would give negative feedback on glucose transport or potentially lead to muscle pathology (8).…”
mentioning
confidence: 99%